2021
DOI: 10.5603/fm.a2020.0079
|View full text |Cite
|
Sign up to set email alerts
|

Types of inferior phrenic arteries: a new point of view based on a cadaveric study

Abstract: Background: The diaphragm is supplied by the superior and inferior phrenic arteries. This present study focusses on the latter. The inferior phrenic arteries (IPA) usually originate from the abdominal aorta. The two arteries have different origins, and knowledge of these is important when performing related surgical interventions and interventional radiological procedures. The aim of this study was to identify variations in the origin of the IPA and conduct relevant morphometric analyses. Materials and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The right and left inferior phrenic arteries normally arise from the aorta or celiac axis independently, or as a common trunk. However, these arteries show several variations depending upon their origin [ 35 , 36 , 37 ]. Understanding the variations of the inferior phrenic artery are important for surgical and radiological interventions in conditions such as hepatocellular carcinoma, traumatic vascular injuries, hemoptysis and gastroesophageal hemorrhage [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The right and left inferior phrenic arteries normally arise from the aorta or celiac axis independently, or as a common trunk. However, these arteries show several variations depending upon their origin [ 35 , 36 , 37 ]. Understanding the variations of the inferior phrenic artery are important for surgical and radiological interventions in conditions such as hepatocellular carcinoma, traumatic vascular injuries, hemoptysis and gastroesophageal hemorrhage [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 In a recent investigation, the LGA is given origin to the inferior RIPA and LIPA, while no celiac trunk was found. 19 In this study, the left IPA was the branch off LGA in 4 % of individuals as existing data. The hepatosplenic trunk, gastrophrenic trunk, splenic hypoplasia and auxiliary spleen were described by Yi et al, 20 whereas Shibamoto et al reported the concurrent existence of the LGA and CHA that courses retroportally called the hepatosplenomesenteric trunk and for both IPAs a common trunk in cancer stomach patient.…”
Section: Discussionmentioning
confidence: 53%
“…Classical dissection techniques were used (Balcerzak et al, 2020; Olewnik et al, 2018; Olewnik, Wysiadecki, Polguj, Waśniewska, et al, 2017; Szewczyk et al, 2020; Waśniewska et al, 2020). During the dissection, the following were observed: the morphology of the SMA, the point where it branched off the abdominal aorta in reference to the spine, the distance to the celiac trunk, the distance to the inferior mesenteric artery, and the distances to the origins of the common iliac arteries and the median sacral artery (MSA).…”
Section: Methodsmentioning
confidence: 99%